Clinical and Demographic Characteristics of Women with Intrauterine Adhesion in Abuja, Nigeria - Efena R. Efetie; Augustine C. Umezulike; Ugochukwu V. Okafor (Obstetrics and Gynecology International)
Objective. Infertility menstrual abnormalities continue to constitute a significant bulk of gynecological consultation in Africa. Both of these problems are sometimes traced to intrauterine adhesions which are preventable in the majority of cases. Study Design. A retrospective analysis of intrauterine adhesions at the National Hospital Abuja, Nigeria, was carried out, covering the period from 1st September 1999 to 1st September 2004. A total of 72 cases were analyzed. Statical analysis was done using 𝑋2. Results. The incidence of intrauterine adhesions was 1.73% of new patients. Mean age ± SD was 29.97±4.82 years. Patients who were Para 0 to 1 constituted 81.9% of the total. Intrauterine adhesions significantly (𝑃<0.02) occurred in nulliparae. The majority (68%) were educated only up to secondary level which was significant (𝑃<0.05). Menstrual abnormalities were present in 90.3%. The commonest predisposing factor identified was a history of dilatation and curettage or uterine evacuation. Conclusion. Intrauterine adhesions are associated with lower educational status and low parity. Increasing educational targets nationally, poverty alleviation, nationwide retraining in manual vacuum aspiration, and wider application of this technique are recommended.